Improved production strain maintenance technique for Burkholderia mallei 5584 (Master seed) used for glander diagnostic agent production - E. A. Artemeva; L. A. Melnikova; L. I. Zaynullin; N. K. Bukova (Ветеринария сегодня)
One of the aspects important for strain collection maintenance is the optimization of existing methods and development of new techniques for microbial strain preservation, that is why the improvement of previously developed methods for authentic strain preservation is an urgent task. The article provides information on the maintenance of Burkholderia mallei 5584 (Master seed) using previously developed technique, which was supplemented with new stages in accordance with modern requirements for strain collections of highly dangerous disease agents. The previous strain maintenance technique involved its storage in its native state, which facilitated accumulation of genetic mutations and, ultimately modification of bacterial cell properties. To extend the storage time of this strain and to ensure the stability of its biological properties, the freeze-drying method was used. Skimmed milk was used as a cryoprotectant. Freeze-drying was performed under selected conditions. This technique allows for the strain sub-culturing on sensitive models once every 5 years, which is more expedient and safe from an economic and biological point of view. For safe handling of Burkholderia mallei 5584 production strain, an inactivation technique using gamma rays at 30 kGy was developed, which allowed to achieve microbial suspension sterility and preserve the bacterial cell structure. When comparing the previously developed and supplemented techniques, it was found that the improved technique of Burkholderia mallei 5584 (Master seed) maintenance makes it possible to avoid the loss of its biological properties needed for the production of high-quality laboratory diagnostic agents used for timely disease detection in susceptible animals by diagnostic tests.